Tele-Instruction Tool for Multiple Lay Responders Providing Cardiopulmonary Resuscitation in Telehealth Emergency Dispatch Services: Mixed Methods Study - Jianing Xu; Mingyu Qu; Xuejie Dong; Yihe Chen; Hongfan Yin; Fangge Qu; Lin Zhang (JMIR Publications, 2023)
BackgroundTelephone-assisted cardiopulmonary resuscitation (T-CPR) has proven to be a crucial intervention in enhancing the ability of lay responders to perform cardiopulmonary resuscitation (CPR) during telehealth emergency services. While the majority of established T-CPR protocols primarily focus on guiding individual rescuers, there is a lack of emphasis on instructing and coordinating multiple lay responders to perform resuscitation collaboratively. ObjectiveThis study aimed to develop an innovative team-based tele-instruction tool to efficiently organize and instruct multiple lay responders on the CPR process and to evaluate the effectiveness and feasibility of the tool. MethodsWe used a mixed methods design in this study. We conducted a randomized controlled simulation trial to conduct the quantitative analysis. The intervention groups used the team-based tele-instruction tool for team resuscitation, while the control groups did not have access to the tool. Baseline resuscitation was performed during the initial phase (phase I test). Subsequently, all teams watched a team-based CPR education training video and finished a 3-person practice session with teaching followed by a posttraining test (phase II test). In the qualitative analysis, we randomly selected an individual from each team and 4 experts in emergency medical services to conduct semistructured interviews. The purpose of these interviews was to evaluate the effectiveness and feasibility of this tool. ResultsThe team-based tele-instruction tool significantly improved the quality of chest compression in both phase I and phase II tests. The average compression rates were more appropriate in the intervention groups compared to the control groups (median 104.5, IQR 98.8-111.8 min-1 vs median 112, IQR 106-120.8 min-1; P=.04 in phase I and median 117.5, IQR 112.3-125 min-1 vs median 111, IQR 105.3-119 min-1; P=.03 in phase II). In the intervention group, there was a delay in the emergency response time compared to that in the control group (time to first chest compression: median 20, IQR 15-24.8 seconds vs median 25, IQR 20.5-40.3 seconds; P=.03; time to open the airway: median 48, IQR 36.3-62 seconds vs median 73.5, IQR 54.5-227.8 seconds; P=.01). However, this delay was partially mitigated after the phase II test. The qualitative results confirmed the compatibility and generalizability of the team-based tele-instruction tool, demonstrating its ability to effectively guide multiple lay responders through teamwork and effective communication with telecommunicators. ConclusionsThe use of the team-based tele-instruction tool offers an effective solution to enhance the quality of chest compression among multiple lay responders. This tool facilitated the organization of resuscitation teams by dispatchers and enabled efficient cooperation. Further assessment of the widespread adoption and practical application of the team-based tele-instruction tools in real-life rescue scenarios within the telehealth emergency services system is warranted.